Some Notes on Popular Music in my (Professional) Life - Nettl, Bruno (Journal of World Popular Music, 2017)
This article sketches the author’s experience with popular music as a student of music and ethnomusicology in the United States, and as a professional in this field. Principally it is a personal meditation on the role of popular music in the history of ethnomusicology, particularly in the Society for Ethnomusicology, in the history of American musical academia, and the reasons for its initial neglect. It recalls some incidents witnessed by the author that were turning points in the eventual acceptance of popular music by both ethnomusicologists and historical musicologists.